2020
DOI: 10.1038/s41408-020-0299-0
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of change in treatment, response, and outcome in patients with follicular lymphoma over the last four decades: a single-center experience

Abstract: Although the introduction of immunotherapy has improved outcomes for follicular lymphoma (FL) patients, histological transformation (HT) and early relapse still confer a poor prognosis. We sought to describe the patterns of change in treatment, response, and outcome of FL patients at our institution over the last four decades. Seven hundred and twenty-seven patients (389 F/338 M; median age, 57 years) consecutively diagnosed with grade 1-3a FL between 1980 and 2017, categorized into four decades according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
(30 reference statements)
1
24
2
Order By: Relevance
“…Other factors include increased susceptibility in acquiring genetic alterations or age [7]. For example, follicular lymphomas are indolent in nature, but they often are associated with a poor prognosis [8]. Certain limitations also arise from utilising the TCGA dataset.…”
mentioning
confidence: 99%
“…Other factors include increased susceptibility in acquiring genetic alterations or age [7]. For example, follicular lymphomas are indolent in nature, but they often are associated with a poor prognosis [8]. Certain limitations also arise from utilising the TCGA dataset.…”
mentioning
confidence: 99%
“…In a study by Conconi et al [ 14 ] that included 281 FL cases from 1979 to 2007, the trend in the proportion of patients aged ≥60 years with stage III/IV disease and high-risk FLIPI scores increased over the study period, although the result was not statistically significant. Mozas et al [ 13 ] studied 727 grade 1–3A FL cases reported between 1980 and 2017, and found that grade 1–2 disease showed a decreasing trend over time, while high-risk FLIPI showed an increasing trend in recent years. These findings can be attributed to the increasing life expectancy and increase in the number of patients that present with advanced FL status at initial diagnosis, as a majority of the patients are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Grade 3B FL or transformation to high-grade B-cell lymphoma significantly reduces survival [11,12]. However, due to the availability and broad use of rituximab, the incidence of transformation has been reduced, and the distribution of clinicopathologic features including histologic grade and FLIPI subgroup has changed, although the differences have not been reported consistently [12][13][14]. Most of the information in the literature is based on studies involving Caucasian patients, and characteristics of FL in East Asians have Upward trend in follicular lymphoma among the Korean population: 10-year experience at a large tertiary institution not been delineated well.…”
mentioning
confidence: 99%
“…1 The introduction of immunotherapy has greatly improved outcomes for FL patients, with a median overall survival (OS) now approaching 20 years. 2,3 However, relapses are continuously seen during follow-up, and responses progressively shorten with each relapse, with a median survival after third-line therapy of 4.8 years. 4 In recent times, new drugs have been developed for B-cell malignancies in general, and for FL in particular, such as the combination of rituximab and lenalidomide for untreated 5 and relapsed/refractory FL, 6 as well as other small molecules and their combinations.…”
Section: The Interval Between Frontline Treatment and The Second Relapse (Pfs2) Predicts Survival From The Second Relapse In Follicular Lmentioning
confidence: 99%